1995
DOI: 10.1590/s0101-81751995000100014
|View full text |Cite
|
Sign up to set email alerts
|

Estudo filogenético de Mesembrinellinae com ênfase no gênero Eumesembrinella Townsend (Diptera, Calliphoridae)

Abstract: ABSTRACT. PHYLOGENETIC STUDY OF MESEMBRINEU.lNAE, WITH EMPHASIS IN (ALDRICH 1922;TOWNSEND 1931TOWNSEND ,1935HALL 1948;MELLO 1967; GUIMARÃES 1977;PERIS & MARILUIS 1984). No entanto, a maioria dos trabalhos realizados ficou restrito apenas aos propósitos de descrição e identificação.Excetuando GUIMARÃES (1977), podemos afirmar praticamente que quase nada foi postulado a respeito das relações filogenéticas intergenéricas para Mesembrinellinae ou interespecíficas para Eumesembrillella Townsend, 1931. No entanto,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1
33

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(59 citation statements)
references
References 6 publications
2
23
1
33
Order By: Relevance
“…Existem poucos estudos sobre esta espécie. Encontra-se distribuída pelo Brasil nos estados do Espírito Santo e Rio de Janeiro (Toma & Carvalho 1995).…”
Section: Resultsunclassified
“…Existem poucos estudos sobre esta espécie. Encontra-se distribuída pelo Brasil nos estados do Espírito Santo e Rio de Janeiro (Toma & Carvalho 1995).…”
Section: Resultsunclassified
“…This is very important, since both species belong to the subfamily Mesembrinellinae, described in the literature as being exclusively Neotropical and resident of dense forests and wetlands (Mello, 1967;Toma and Carvalho, 1995). Therefore, the PARNA Tijuca has the conditions for the establishment of forest species in the more internal areas.…”
Section: Speciesmentioning
confidence: 99%
“…In the current study and in the previous one (Ferraz et al, 2010b), this species showed a negative correlation with precipitation, i.e., it is more abundant during periods of low rainfall. In Brazil, M. semihyalina occurs in the states of Espírito Santo and Rio de Janeiro (Toma and Carvalho, 1995).…”
Section: Species Distribution: Edge Effects × Seasonalitymentioning
confidence: 99%
“…The Mesembrinellinae is a small group of exclusively Neotropical flies (Toma and Carvalho, 1995), limited to rain forest habitats (Guimarães et al, 1978), dense forests and wetlands, especially at low altitudes (Mello, 1967). Work involving this group has been restricted to description, and no surveys have specifically targeted it (Marinho et al, 2006;Ferraz et al, 2009;Mello et al, 2009;Amat, 2010).…”
Section: Introductionmentioning
confidence: 99%